Graph-Based Technique for Searching Structured Databases - Hassan, Mohammad (International Journal of Engineering and Technology, 2018)
This paper presents a graph-based technique for searching structured or relational databases using keyword queries in a similar wayto search text files using search engines. Our approach depends on identifying first the data within a database that are most likely to provide the useful result to the raised query and then search only the identified data. The proposed search algorithm uses an undirected weighted graph data structure for implementing the search process. To construct the graph, we introduced a modified function for computing edge weights which measure the connections among vertices in the graph. Experiments and the prototype implementation on real datasets prove that the proposed model is feasible and supports searching relational databases using keyword queries.